Pengaruh Struktur Aset dan Ukuran Perusahaan Terhadap Struktur Modal pada Perusahaan Manufaktur - Elinda Febri Kharismawati; Faisal Fikri Nazarudin; Trisa Indrawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
study aims to find out how the description of asset structure, company size, and capital structure. To determine the effect of asset structure and company size partially and simultaneously on the capital structure of companies listed on the IDX. This research method is multiple linear regression analysis using SPSS version 25. The population in this study were 30 companies. The results showed that the asset structure, company size and capital structure in companies listed on the Indonesia Stock Exchange all increased annually. The asset structure and size of the company have no effect on the capital structure of the Company listed on the IDX. The asset structure and size of the company simultaneously have no effect on the capital structure of the Company listed on the IDX.